FRI0086 Is the discordance between the doctor and the patient a determinant of adherence?. (12th June 2018) - Oton, T.; Calvo-Alén, J.; Cea-Calvo, L.; Carmona, L.
Abstract : Background: Adherence is a critical factor in the therapeutic response in rheumatoid arthritis (RA), which may be influenced by the doctor-patient relationship. In the ARCO study, we previously reported a percentage of lack of adherence to the subcutaneous biologic of 14.3% during the first 14 months of treatment, and that the adherence was better in patients without induction and with a monthly administration schedule. 1 In this post hoc analysis, we explored whether doctor-patient disagreements may be related to lower adherence rates. Objectives: To analyse the percentage of patients with discrepancies in the evaluation of the activity of the disease between doctors and patients and a possible association between the existence of disagreement and adherence to subcutaneous biological drugs. Methods: The ARCO study was a multicenter, cross-sectional study in which patients with RA were included according to EULAR-ACR 2010 criteria, who had been prescribed a subcutaneous biological drug in the previous 12–18 months. As part of the evaluation of the disease, patients and doctors were asked to rate the disease on a visual analogue scale (VAS), with values ranging from 0 to 10; with higher values indicating worst symptoms. Disagreement was defined as a difference of >/=3 points between the absolute values. Adherence was assessed retrospectively by means of the Medication Posession Ratio (MPR), considering adherence those patients with MPR >80%. The association between adherence and disagreement was studied using bi and multivariate logistic regression models with covariates-adjustments. Results: We included 360 patients (77.5% women, mean age: 55±0.6 years). Disagreement was detected in 56 (15.5%). In patients with disagreement, the mean VAS score of the patient was 5.75±1.8 versus 2.7±2.2 in the group without disagreement (p<0.001), and there were no differences in terms of the doctors VAS (group with disagreement=2.7±1.8 versus 2.2±2.0 in the group without disagreement, p=0.110). The two groups of patients presented differences in terms of age (5 years more than average in the group with disagreement, p=0.010), presence of comorbidity (14% more frequent in the group with disagreement, p=0.030) and the value of the mean DAS28 (0.6 points higher in the group with disagreement, p<0.001). Among the patients who presented a VAS disagreement, the percentage of non-adherence was 10.7%, and of 14.5% among those who had a VAS similar to the doctor (p=0.45). The regression analysis showed no difference in the association between adherence and disagreement; by introducing into the models covariates associated with adherence (induction, frequency of administration and age) or with disagreement (age, comorbidity and DAS28). Conclusions: We observed a disagreement between patients and doctor VAS scores in 15.5% of cases, with higher values coming from patients. We did not observed an association between this disagreement and adherence to subcutaneous biological drugs. Reference: [1] Calvo-Alen J, Monteagudo I, Salvador G, Vazquez-Rodriguez TR, Tovar-Beltran JV, Vela P, et al. Non-adherence to subcutaneous biological medication in patients with rheumatoid arthritis: a multicentre, non-interventional study. Clin Exp Rheumatol2017;35(3):423–30. Acknowledgements: This is a secondary analysis of the ARCO study, which was financed by Merck Sharp and Dohme Spain. Disclosure of Interest: T. Oton: None declared, J. Calvo-Alén : None declared, L. Cea-Calvo Employee of: Merck Sharp and Dohme S.A, L. Carmona: None declared